(3GdefgL GdeSdhc aj SjGSI Gdedhcs - (3YHO GdQMef Hf fUQ Hf YHO Gddg, CHh GdfLjH, LdGd GdOjf GdYOhj GdTjRQj, fMh (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YLRJ GdYbhd Yf eYQaI PGJg deG cGf Gdehdi Gdedc GdfGUQ UdGM GdOjf hGdOjf CHh GdeXaQ LeYJ dNRGfI Ydheg gPG GdcJGH s
(3BNQgG (B:s
(3hCeG GdWHbI GdKGdKI ef Gdedhc age GdGcKQhf bdhHge bSjI hCfaSge YUjI jDKQhf GddPGJ Ydi CehQ GdOjGfGJ hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjI HChdgG dhMI ePgHI cJH YdjgG GSe GdcJGH hGSe GdeDda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B592s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs